Intelligence and Slave Export Intensity: A Cross-Country Empirical Assessment - Simplice A. Asongu; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2015)
The literature has not sufficiently engaged the emergence and expansion of the phenomenon of Slave export. This article contributes to the existing stream by examining the role of human capital or intelligence on slave exports. We postulate and justify a reasonable hypothesis that countries which were endowed with higher human capital levels were more likely to experience lower levels of slave exports probably due to relatively better abilities to organise, corporate, oversee and confront slave vendors. Our findings with alternative specifications involving varying conditioning information sets confirm the investigated hypothesis. The findings are also robust to the control of outliers.
Keywords: I20; I29; N30; 330; Intelligence; Human Capital; Slavery